Effect of different processing method and frozen storage on chemical properties of the various parts of the cod head - Aníta Elíasdóttir 1991- (2019)
Cod heads have been dried for decades in Iceland, and most of the products are exported to Nigeria. However, the market in Nigeria is unstable, and therefore, it is not possible to rely on that market alone. It is therefore important to look at other ways to utilize the cod head. The aim of this project was to examine the possibility of utilizing the various parts of the cod head, as well as to investigate the effect of different processing method on board of the fishing vessel and frozen storage on the chemical properties of various parts of cod head i.e. gills, cheeks, tongue, eyes, and brain. The project was divided into two experiments. In experiment I, the effect of different bleeding methods (gill cut, throat cut, and bled and gutted at the same time) and frozen storage (-25°C) on the gills, cheeks, tongue, eyes, and brain were examined. In experiment II, the effect of different chilling methods (chilling with ice and superchilling) and with frozen storage (-25°C) was examined on the gills. The results from this study showed that different bleeding method did not overall affect the chemical properties in the various parts of the cod head. However, during frozen storage, chemical changes were observed in the various parts of the cod head. During frozen storage, the amount of free fatty acids increased. Different chilling did not affect the chemical properties of the gills. The highest protein content was observed in the cheeks, or 16.7% and the highest lipid content in the brain, or 8.0%, both after 2 weeks of frozen storage. The results showed that the gills contain a decent amount of minerals, especially potassium, calcium, and phosphorus. The results show that there is a great potential to produce value-added products, especially from the gills regarding the high amount of minerals and high protein content. Þurrkun á þorskhausum hefur verið stundað um árabil á Íslandi og eru flestar vörurnar fluttar út til Nígeríu. Hins vegar er markaðurinn í Nigeríu óstöðugur og því ekki hægt að treysta á þann markað ...